Histopathological study of lung cancer: Rate of different types of bronchogenic carcinoma of follow up cases in Benghazi Medical Centre - Al-Taleb, Ramzi; Zoubi, Salha; Al-Gheryani, Nabeia (Benghazi University Medical Journal, 2024)
Introduction: Lung cancer has transformed from a relatively rare disease to a worldwide health problem and a major global health concern. It is the second most common cancer in both men and women, after prostate and breast cancer respectively. It has become the leading cause of cancer-related death. Aim: This study is conducted to shed the light on the rate of different types of lung cancer among patients who were diagnosed and treated at Benghazi Medical Center. Material and methods: The current study was a retrospective study, carried on 269 Case of confirmed primary lung cancer diagnosed between the years 2015, to 2018. Data was collected from the Oncology Department of Benghazi Medical Center. The data was analyzed using SPSS version 23, and was plotted into tables and figures by Microsoft Excel 2010. Results: This study revealed that the common age group of patients was between 61–70 years, with a mean age of 62.3±3.75 (SD) years. The disease was more common in males than females. Most of the patients were active smokers, and about 92.9% of the patients have no past medical history of respiratory diseases. Non-small cell carcinoma was the commonest type of lung cancer (71.4%), out of which adenocarcinoma represented 54% of the cases. Almost all (92.9%) cases were presented with stage IV of the cancer at the time of diagnosis, which meant that the cancer was already metastasized to distant organs. In about 72.5% of the cases, the tumor was in the right side of the lung, in the upper region. There was a statistically significant difference between the mean age of males and females. Also, there was a significant relationship between the adenocarcinoma subtype of NSCLC (None Small Cell Lung Cancer) and patients with no past respiratory diseases. Conclusion: lung cancer is an aggressive malignant tumor which was very common among smoking Libyan males and usually associated with high mortality rate.